Divergent Reactivity of Stannane and Silane in the Trifluoromethylation of PdII: Cyclic Transition State versus Difluorocarbene Release. Issue 46 (17th October 2018) - Pu, Maoping; Sanhueza, Italo A.; Senol, Erdem; Schoenebeck, Franziska
Abstract: The transmetalation is a key elementary step in cross‐coupling reactions. Yet, the precise nature of its mechanism and transition state geometry are frequently elusive. This report discloses our study of the transmetalation of [Pd II ]‐F complexes with the silane‐ and stannane‐based trifluoromethylation agents, R3 SiCF3 and R3 SnCF3 . A divergent reactivity was uncovered, with the stannane showing selective R‐group transfer, and the silane selective CF3 ‐group transfer. Using a combined experimental and computational approach, we uncovered a hitherto unrecognized transmetalation mechanism with the widely employed R3 SiCF3 reagent, explaining its unique activity in metal‐catalyzed trifluoromethylations. While the stannane reacts via a cyclic, 4‐membered transition state, the silane undergoes a fundamentally different pathway and releases a difluorocarbene in the transmetalation event. Molecular dynamics studies clearly reinforced the liberation of a free CF2 carbene, which reacts with [Pd II ]‐F to ultimately generate [Pd II ]‐CF3. Abstract : Transmetalation is a key elementary step in cross‐coupling reactions. The precise nature of its mechanism and transition state geometry are frequently elusive. This Communication discloses studies of the transmetalation of [Pd II ]‐F complexes with the silane‐ and stannane‐based trifluoromethylation agents R3 SiCF3 and R3 SnCF3 .